The Inflammatory Actions of Coagulant and Fibrinolytic Proteases in Disease - Michael Schuliga (Mediators of Inflammation)
Aside from their role in hemostasis, coagulant and fibrinolytic proteases are important mediators of inflammation in diseases such as asthma, atherosclerosis, rheumatoid arthritis, and cancer. The blood circulating zymogens of these proteases enter damaged tissue as a consequence of vascular leak or rupture to become activated and contribute to extravascular coagulation or fibrinolysis. The coagulants, factor Xa (FXa), factor VIIa (FVIIa), tissue factor, and thrombin, also evoke cell-mediated actions on structural cells (e.g., fibroblasts and smooth muscle cells) or inflammatory cells (e.g., macrophages) via the proteolytic activation of protease-activated receptors (PARs). Plasmin, the principle enzymatic mediator of fibrinolysis, also forms toll-like receptor-4 (TLR-4) activating fibrin degradation products (FDPs) and can release latent-matrix bound growth factors such as transforming growth factor-β (TGF-β). Furthermore, the proteases that convert plasminogen into plasmin (e.g., urokinase plasminogen activator) evoke plasmin-independent proinflammatory actions involving coreceptor activation. Selectively targeting the receptor-mediated actions of hemostatic proteases is a strategy that may be used to treat inflammatory disease without the bleeding complications of conventional anticoagulant therapies. The mechanisms by which proteases of the coagulant and fibrinolytic systems contribute to extravascular inflammation in disease will be considered in this review.